Should we protect people with ADHD from playing? A review on the association between Attention-Deficit/Hyperactivity Disorder and Internet Gaming Disorder. - Isa Cristina Duarte Barbosa (2020)
Introduction: Since Internet Gaming Disorder was included in the Fifth Edition of Diagnostic and Statistical Manual of Mental Disorders (DSM-5), there is a growing body of literature concerning this issue. Most studies have focused generally on the comorbidities linked to pathological gaming, while there have been a few focusing specifically on Attention-Deficit/Hyperactivity Disorder (ADHD). This review aims to review the knowledge concerning the association between ADHD and pathological gaming and the existing gaps. Methods: Relevant literature on data included in this review were identified through a search of Pubmed in relation to pathological gaming and ADHD for articles in English until September 2019. Additional literature about internet addiction was included when gaming content was considered relevant. Variables influencing the association, underlying mechanisms and consequences in the future were also discussed. Results: Since DSM-5 included IGD, the OR for pathological gaming in ADHD ranged between 1.27 and 13.51. Figure 1 shows the possible factors mediating this association. The literature proposes impulsivity, hostility, inattention, social skills deficits and poor inhibitory control as mediators, based on ADHD lack of dopamine suppressed by gaming, when it activates brain's dopamine reward system. The association between ADHD symptoms and gaming disorder suggests a vicious cycle that can negatively affect varied life dimensions, raising the importance of controlling time playing of ADHD patients. Conclusions: Attention-Deficit/Hyperactivity Disorder seems to increase the risk of pathological gaming when compared to healthy population, but the directionality remains unclear because of methodological weaknesses in the studies.